Self regulation and discipline development to improve independence students in English course - Jumiati Siska; Meydia Afrina; Okky Leo Agusta; Rambat Nur Sasongko; Muhammad Kristiawan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The development of self-regulation and discipline can affect the way children learn independently. The independence of children's learning allows them to become individuals who are able to complete the independent way of the child's own personality. The purpose of this study is to see self-regulation of English subjects at the junior high school level. This study uses a quantitative approach with the type of ex post facto research. which was carried out at SMPN 2 Bengkulu City with a sample of 30 students specifically for English lessons. Data collection was done by using numbers and analyzed through regression analysis. The results of this study indicate that self-regulation partially or not affect students' learning independence; discipline towards student learning independence; as well as self-regulation and discipline towards student learning independence, especially in English subjects. This paper provides teachers to be more creative and implement student-centered learning. Optimizing discipline by providing fair and collective rewards.